Promoting Well-being and Tackling Educational Poverty: A Narrative Synthesis - Nicoletta Di Genova; Sara Baroni (Pensa MultiMedia, 2022)
The contribution presents a narrative synthesis of the literature on the concepts of poverty and well-being, assumed in their multidimensional character, considering the consequences of the pandemic emergency. The aim is to identify among the recent pedagogical literature the dimensions that should be addressed in order to develop educational pathways aimed at ensuring equality. We also intend to reflect on the role of teachers and educational communities to plan these pathways. The process of researching the literature on the adressed issues has produced a collection of 12 articles that have been analyzed using the software MAXQDA. Here we illustrate the multiple dimensions that emerged at the individual and community level, their interconnections and pedagogical implications for educational theory and practice.